Confusion Analysis and Detection for Workflow Nets - Xiao-liang Chen; Zhong-yuan Jiang; Jian-hong Ye (Discrete Dynamics in Nature and Society)
Option processes often occur in a business procedure with respect to resource competition. In a business procedure modeled with a workflow net (WF-net), all decision behavior and option operations for business tasks are modeled and performed by the conflicts in corresponding WF-net. Concurrency in WF-nets is applied to keep a high-performance operation of business procedures. However, the firing of concurrent transitions in a WF-net may lead to the disappearance of conflicts in the WF-net. The phenomenon is usually called confusions that produces difficulties for the resolution of conflicts. This paper investigates confusion detection problems in WF-nets. First, confusions are formalized as a class of marked subnets with special conflicting and concurrent features. Second, a detection approach based on the characteristics of confusion subnets and the integer linear programming (ILP) is developed, which is not required to compute the reachability graph of a WF-net. Examples of the confusion detection in WF-nets are presented. Finally, the impact of confusions on the properties of WF-nets is specified.